Proceedings - ICPM 2008; International Conference on Precision Measurement; 08-12 September 2008; Ilmenau University of Technology (SLE,Univ.-Bibliothek der TU, 2008)
The International Program Committee of the International Conferemce on Precision Measuarement 2008 warmly welcome you to this conference being held at the iImeneau of the Technology, Germany, from 8-12 September 2008